2016
DOI: 10.3390/ijms17040568
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of MicroRNAs in Preoperative Treated Rectal Cancer

Abstract: Background: Patients with locally advanced rectal cancer are treated with preoperative chemoradiotherapy followed by surgical resection. Despite similar clinical parameters (uT2-3, uN+) and standard therapy, patients’ prognoses differ widely. A possible prediction of prognosis through microRNAs as biomarkers out of treatment-naïve biopsies would allow individualized therapy options. Methods: Microarray analysis of 45 microdissected preoperative biopsies from patients with rectal cancer was performed to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 85 publications
0
19
0
Order By: Relevance
“…In rectal cancer, miR-92a expression is inversely associated with KLF4 and IQGAP2 expression [14]. miR-573,miR-579 and miR-802 display the significant correlation with overall survival of patients, in addition to, miR-573 is significantly correlated with tumor grade of patients after preoperative chemoradiotherapy [15]. In patients with rectal adenocarcinoma, serum level of miR-125b is significantly over-expressed in pCRT non-responders compared to those responders [16].…”
Section: Introductionmentioning
confidence: 99%
“…In rectal cancer, miR-92a expression is inversely associated with KLF4 and IQGAP2 expression [14]. miR-573,miR-579 and miR-802 display the significant correlation with overall survival of patients, in addition to, miR-573 is significantly correlated with tumor grade of patients after preoperative chemoradiotherapy [15]. In patients with rectal adenocarcinoma, serum level of miR-125b is significantly over-expressed in pCRT non-responders compared to those responders [16].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In colorectal cancer, a series of miRNAs have been investigated to serve either as a tumor suppressor role or oncogenic driver. 21 Among these miRNAs, miR-143 and miR-145 are initially explored to play a tumor suppressor role in colorectal cancer. 10,22 In addition, miR-101, miR-133b, miR-126 and miR-142-3p are all served as a tumor suppressor in colorectal cancer, while miR-21 and miR-106a expression are significantly higher in the stool of the colorectal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…A study indicated that interrupting miR-579 binding affinity may increase the risk of breast cancer [23]. miR-579 was obviously associated with overall survival and tumor-specific survival of patients with locally advanced rectal cancer [32]. Upregulation of miR-579 could block proliferation, cell cycle, migration and also trigger the apoptosis of glioblastoma multiform cells [24].…”
Section: Discussionmentioning
confidence: 99%